Pengembangan Perilaku Prososial Peserta Didik melalui Layanan Dasar Bimbingan - Rahimsyah, Anandha Putri; Ilfiandra, Ilfiandra (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2017)
This study aimed to test the effectiveness of guidance curriculum to develop studentsâ pro-social behavior. This was a quasi-experimental study with non-equivalent pretest-posttest control group design. The sample of this study was the 25 students of IVb SD IT Ibnu Khaldun Lembang. It was taken by using convenient sampling technique. The instruments of this study were pro-social behavioral response questionnaire. The data were analyzed by using Anacova. The result of the statistical test showed that the guidance curriculum has not been effective to develop the studentsâ pro-social behavior. However, practically, the guidance curriculum is able to create studentsâ pro-social behavior, it was proven by the experimental group studentsâ score improvement compared to the control group. Moreover, it could be observed qualitatively through the result of the observation, interview, and self-checklist.Â  The most dominant qualitative changes shown by the behavioral aspects of teamwork, sharing, or giving in the form of information sharing, time-sharing, material sharing, and helping such as amusing friends. This study generated a new strategy for elementary school counselor in designing and implementing a guidance curriculum that is integrated with the guidance-nuanced learning process to improve the studentsâ pro-social behaviorâ essential aspects.